Physiological Response and Behavioral Patterns of Ettawa Crossbred Goats (PE) to the Environmental Conditions of Mount Sangiang - Wandira, Ica Ayu; Sadia, I Nyoman; Dohi, Muhammad; Karni, Ine (Jurnal Biologi Tropis, 2025)
The adaptive capacity of animals is a crucial factor in maintaining survival and productivity, particularly within sustainable livestock systems in tropical regions under climatic stress. This study aimed to analyze the physiological responses and daily behavioral patterns of Ettawa Crossbred (PE) goats to the environmental conditions of Mount Sangiang, Wera District, Bima Regency. The research was conducted using an observational descriptive approach with samples of PE goats from various age groups and sexes. Physiological parameters observed included body temperature, respiratory rate, and heart rate, while behavioral aspects covered feeding, drinking, resting, exploration, and social interaction. The results showed that PE goats were able to maintain body temperature within the normal range (36–38°C), even when daytime environmental temperatures reached 32°C. Adjustments in respiratory rate and heart rate served as the primary mechanisms for coping with heat stress, with younger goats tending to be more sensitive than adults. In terms of behavior, PE goats grazed in the morning and afternoon when temperatures were cooler, while midday was used for resting and drinking to minimize the risk of heat stress. Exploration of the savanna was carried out to meet feed requirements, while social interactions occurred more frequently at night in the cooler and more humid coastal areas. Overall, PE goats demonstrated strong physiological and behavioral adaptability to the environmental conditions of Mount Sangiang.